The Psychometric Properties of the Academic Self-Esteem Scale - Bangla - L. Naher; M.A. Asma; O. Ahmed (University of Sofia, 2019)
The academic self-esteem is one of the key factors for better academic achievement. However, there is a scarcity of available measures for assessing students' academic self-esteem. The present study was undertaken to assess psychometric properties of the Academic Self-Esteem Scale (ASES) for use in Bangladesh context. The ASES was translated into Bangla following the guidelines of International Test Commission and the translated version was administered on a sample of 221 students who were selected from different universities via convenience sampling technique. Results explored that all items except one item of the ASES had sufficient item-total correlations. Exploratory factor analysis revealed only one component that met the criteria for inclu-sion as a factor. This scale has good internal consistency reliabilities, test-retest reliability, composite reliability, average variance extracted (AVE), standard error of measurement, and predictive validity. Differential item functioning test results suggested absence of item response bias between high and low achiever groups. This scale would be helpful to researchers, teachers, guardians, and students to assess their academic self-esteem.